IMPACT OF POLITICAL CULTURE ON THE POLICY-MAKING PROCESS: COMPARATIVE ANALYSIS OF THE UNITED KINGDOM AND TÜRKIYE - Aydilek, Emre (Marmara University, 2024)
Questioning the codes, sociological tendencies, fields of social conflict/ harmony of a country’s political culture is essential in identifying the problems of that country’s political, social, and human life. All these parameters, such as determining values, symbols, and tendencies in political culture, directly or indirectly affect the policy-making process of countries. This study focuses on the effects of political culture on policy making in the United Kingdom (UK) and Türkiye, trying to understand the differences and similarities in this area and includes extensive comparative analysis. The main problem of this research is whether phenomena can be transferred from the UK to Türkiye in terms of political culture to solve political and social issues in Türkiye. The hypothesis derived from this research question is that Türkiye’s political culture and institutions have been politicized as a historical tradition, especially in recent years. In this context, the study aims to contribute to an under-researched area of comparative political science and literature by providing insights into the political dynamics of Türkiye and the UK. The study’s methodology and explanations of the literature on political culture, integrated with analyses of selected cases, provide a framework for understanding and comparing Türkiye’s political culture with that of the UK. These efforts can be seen as an insufficient but essential step towards solving the problems of Türkiye’s political culture.
Keywords: 16. Peace & justice